Video analysis of ACL injuries in football - Krosshaug, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
A precise description of the injury mechanism is critical for the development of effective preventive measures for ACL injuries. Video analysis is the only way to systematically collect kinematic information from real injury situations. We have therefore analyzed 39 cases of ACL injuries in professional football where the injury mechanism was assessed through a description of the match situation and playeropponent behavior. However, a detailed biomechanical assessment is not possible using a visual assessment. For this reason, we developed a Model-Based Image-Matching technique to reconstruct the kinematics of the injured person. In this method, 3D models of the surroundings as well as a customized skeleton model are manually matched to the background video footage. With this technique, it is possible to produce estimate temporal joint angle histories, velocities and accelerations, which are necessary for detailed biomechanical analyses of the injury mechanism. After a 10-year effort to collect and analyze videos of 10 ACL injury situations that were filmed with at least two cameras, we found surprisingly consistent knee kinematics in the impact phase of the injury situation. All the 10 players showed immediate valgus motion within 40 ms after initial contact. Moreover, the tibia rotated internally during the first 40 ms. These results, in combination with other important findings in the literature, led us to propose a new hypothesis for the mechanism of ACL injuries.